2000
DOI: 10.1139/z00-095
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of anthropogenic habitat disturbance on a lizard assemblage inhabiting coastal dunes in Argentina

Abstract: We studied abundance and habitat use in two species of Liolaemus (Squamata: Tropiduridae) at a coastal dune site in eastern Argentina before and 7 years after a road was built at the site. Before disturbance, lizards exhibited similar abundances and a wide segregation in microhabitat use. Liolaemus multimaculatus used flat dunes scarcely covered by Spartina ciliata, while Liolaemus gracilis used the grass Panicum racemosum as cover. After disturbance, the mean number of L. multimaculatus detected by month was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 5 publications
1
30
0
2
Order By: Relevance
“…In this study, the observed changes in the vegetation may affect habitat selection by lizards by increasing temperature, which may influence lizards' thermoregulatory behaviour (Vitt et al 2007), and by changing microhabitat availability (Vega et al 2000). For example, while heliothermal lizards (K. viridistriga, T. oculatus and C. schreibersii) show preferences for open habitats (Cei 1993) because of the high solar radiation, other lizards with preference for habitats with forest cover (O. intermedius, T. merianae and M. dorsivittata) might require high moisture and greater shade (Vitt et al 1998).…”
Section: Discussionmentioning
confidence: 91%
“…In this study, the observed changes in the vegetation may affect habitat selection by lizards by increasing temperature, which may influence lizards' thermoregulatory behaviour (Vitt et al 2007), and by changing microhabitat availability (Vega et al 2000). For example, while heliothermal lizards (K. viridistriga, T. oculatus and C. schreibersii) show preferences for open habitats (Cei 1993) because of the high solar radiation, other lizards with preference for habitats with forest cover (O. intermedius, T. merianae and M. dorsivittata) might require high moisture and greater shade (Vitt et al 1998).…”
Section: Discussionmentioning
confidence: 91%
“…In the light of our results, we suggest that in the conservation management of A. k. fitzingeri, the population interactions within a focal lizard assemblage cannot be disregarded. In anthropogenically-disturbed habitats, the disturbance due to habitat conversion might change the strength of the interpopulation interactions in many ways (Vega et al 2000;Taylor & Fox 2001) possibly causing declines in populations of this potentially endangered subspecies.…”
Section: Discussionmentioning
confidence: 99%
“…From this work it was suggested that space, time and diet are perhaps the most important limiting factors where segregation in lizard assemblages could be detected (e.g., Schoener 1968;Pianka 1973;Toft 1985;Vrcibradic & Rocha 1996). The tools developed in these studies are widely used to answer conservation questions (e.g., Sartorius et al 1999;Vega et al 2000) or for describing the ecological requirements of endangered species (e.g., Martín & Salvador 1995). In this paper, we present the first report of microhabitat use, seasonal activity and diet of the snake-eyed skink.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, assessing lizards' response to changes in habitat availability, especially when the habitats they prefer are unavailable, provides an important indicator of behavioral and physiological plasticity. It has been reported that mi- (Vega, Bellagamba and Fitzgerald, 2000). Therefore, understanding the associations between species abundance and microhabitat characteristics has a considerable conservation value, since it allows ecologists to make predictions about a species' responses to anthropogenic and natural changes in habitat (Martin and Salvador, 1995;Law and Dickman, 1998).…”
Section: Introductionmentioning
confidence: 99%